Molecular identification, incidence and phylogenetic analysis of seven viruses infecting garlic in Ethiopia - Abraham, Adane D.; Kidanemariam, Dawit B.; Holton, T.A. (Springer, 2019)
Little information exists on the type and incidence of viruses infecting garlic (Allium sativum L) in Ethiopia. Attempts were made to identify the viruses using molecular techniques from 95 composite leaf samples collected from 44 farmers' fields and 51 germplasm accessions. Reverse transcription (RT-) PCR using genus and/or virus specific primers was used to amplify partial genome sequences of potyviruses, allexiviruses, carlaviruses and a tospovirus followed by sequencing of PCR products. Results indicated that ~73.7% of the samples are infected with at least one virus. Onion yellow dwarf virus (OYDV, genus Potyvirus, family Potyviridae) is the most common virus detected followed by Garlic virus C (genus Allexivirus) and Shallot latent virus (SLV, genus Carlavirus). Other viruses detected at lower frequency include Garlic virus X and Garlic virus D (genus Allexivirus), Leek yellow stripe virus (genus Potyvirus) and Iris yellow spot virus (IYSV, genus Tospovirus). Mixed infection of two or more viruses was detected in 65.7% of the samples. Phylogenetic analysis suggested that the different viruses may have been introduced to Ethiopia from Europe or Asia. This is the first report of Garlic virus X, Garlic virus D, IYSV and SLV in garlic in Ethiopia. The high incidence of OYDV and IYSV which cause severe yield loss alone or in mixed infection with allexiviruses and carlaviruses is a cause of concern to growers.